Serum procalcitonin in bacterial & non-bacterial meningitis in children - Shipra Chaudhary; Nisha Keshary Bhatta; Madhab Lamsal; Rajendra Kumar Chaudhari; Basudha Khanal (BMC, 2018)
Abstract Background Bacterial meningitis is a paediatric emergency with high mortality and morbidity requiring prompt diagnosis and treatment. Clinically, it is often difficult to differentiate between bacterial and non-bacterial meningitis. Several studies have demonstrated the raised values of serum procalcitonin (PCT) in bacterial infections including meningitis but without definite cut-off guidelines. Hence, this study was done to evaluate serum PCT as a marker to differentiate bacterial and non-bacterial meningitis in children and assess its efficacy. Methods It was a cross-sectional study done over a period of 5 months (Aug 2016-Dec 2016) in the department of Paediatrics, B P Koirala Institute of Health Sciences (BPKIHS). Fifty children aged 3 months to 15 years with suspected meningitis were enrolled and investigated with relevant investigations like complete blood counts, and cerebrospinal fluid (CSF) analysis along with serum PCT. Patients were classified into bacterial (22) and non-bacterial meningitis (28) according to clinical & CSF findings and data analysed using SPSS software. Results Serum PCT levels were significantly higher in bacterial meningitis group (median = 2.04 (1.2-3.18) ng/ml) compared with non-bacterial meningitis (median = 0.35 (0.18-0.35) ng/ml); p < 0.001. The sensitivity and specificity of serum PCT in diagnosis of bacterial meningitis at cut-off level of 0.5 ng/ml were 95.45% and 84.61% respectively. Procalcitonin showed maximum area under receiver operating characteristics (ROC) curve 0.991 (0.974-1.00) (p < 0.001) compared to total leukocyte count and CSF cytochemistry. Conclusion Serum PCT has high sensitivity and specificity for early diagnosis of bacterial meningitis in children. Hence it can be a useful adjunct in differentiating bacterial and non-bacterial meningitis for prompt and better management of the children.